Antidiabetic effect of Psychotria malayana Jack in induced type 1 diabetic rat - Fairuz, Fairuz; Dewi, Hasna; Humaryanto, Humaryanto (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
Background: Therapies for hyperglycemic treatment, including insulin and oral diabetes medications, have been confirmed to cause several side effects. Thus, finding new drugs with fewer side effects is of high importance. Salung leaf herb (Psychotria malayana Jack) reported used in traditional societies as a treatment for diabetes. However, the scientific proof of this plant for diabetes treatment is still lacking. Objective: To evaluate the antidiabetic effect of the P. malayana jack in induced type 1 diabetic rats by assessing blood glucose level and pancreatic cells in white rats. Methods: Alloxan used to induce type I diabetes. Rats randomly divided into six groups. A Group P1 received 250 mg/kg BW; group P2 received 500 mg/kg BW, group P3 received 1000 mg/kg BW. While group 4 basal received no treatment, group 5 received distilled water as a negative control, and group 6 received glibenclamide as a positive control. Medications are given for six days. Glucose levels were measured, and observation of pancreatic Langerhans cell damages. Results:Â  A decrease in blood glucose levels observed in all treatment groups. The most significant reduction (49.76%; 1000 mg/kg BW) occurred in the P3 group. Morphological features of pancreatic Langerhans cell damage were slightly high in the P1 group. Conclusion: P. malayana Jack can consider having an antidiabetic effect in a type 1 diabetic rat by reducing blood glucose levels.